The Power of the Pill for the Next Generation: Oral Contraception's Effects on Fertility, Abortion, and Maternal and Child Characteristics - Ananat, Elizabeth Oltmans; Hungerman, Daniel M. (The Review of Economics and Statistics, 2012)
This paper considers how oral contraception's diffusion to young unmarried women affected the number and parental characteristics of children born to these women. In the short-term, pill access caused declines in fertility and increases in both the share of children born with low birthweight and the share born to poor households. In the long-term, access led to negligible changes in fertility while increasing the share of children with college-educated mothers and decreasing the share with divorced mothers. The short-term effects appear to be driven by upwardly-mobile women opting out of early childbearing while the long-term effects appear to be driven by a retiming of births to later ages. These effects differ from those of abortion legalization, although we find suggestive evidence that pill diffusion lowered abortions. Our results suggest that abortion and the pill are on average used for different purposes by different women, but on the margin some women substitute from abortion towards the pill when both are available. JELNo. I0, J13, N12.